Literacy Applications for Today's Learner - Vickie Johnston; Michael Lancellot (The Advocate, 2015)
Common Core English Language Arts Standards and changing technologies have shifted the ways students and teachers select and read text. Reasons for the lack of digital literacy implementation in instruction are due to the large amount of choices available without sufficient background information on how to critically evaluate literacy applications. This article presents the framework of the Common Core English Language Arts Standards and how they are used to enhance literacy instruction through implementation of literacy technology applications. Limitations and advantages of digital applications are explored, descriptions of the applications are provided, and strategies for implementation in the English/Language Arts classroom are discussed.